Phase Change Memory Device Physics, Reliability and Applications (Springer International Publishing, 2018)
This book describes the physics of phase change memory devices, starting from basic operation to reliability issues. The book gives a comprehensive overlook of PCM with particular attention to the electrical transport and the phase transition physics between the two states. The book also contains design engineering details on PCM cell architecture, PCM cell arrays (including electrical circuit management), as well as the full spectrum of possible future applications.